MAQAM TAWAKKAL DALAM ALQURAN (KAJIAN PERSPEKTIF IMAM ALUSI DALAM TAFSIR RUHUL MA’ANI FI TAFSIR ALQURAN AL-’AZIM WA SAB’I AL-MATSANI) - Akhdiat, Akhdiat; Marisa, Siti Nurkhafifah; Faisal, Muhammad (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
Tawakal is a concept in Sufism that sometimes relies on other than Allah, so that the essence of tawakkal itself is not obtained. Ruh al-Ma'ani is one of the books of interpretation with an isyari interpretation approach, so it is very suitable to be used in explaining Sufistic things. The purpose of this study is to describe the views of Imam Alusi in interpreting the verses about the essence of tawakal in his interpretation book. The method used in this research is library research in which the presentation uses descriptive-analytic method. The results of this research found that in the Book of Tafsir, Ruh al-Ma'ani tawakal is defined as holding on, entrusting and leaving all affairs only to Allah but still carrying out endeavors as much as possible, and relying on Allah as the Protector. Furthermore, tawakkal must be accompanied by faith and vice versa, faith is realized with tawakkal.